Improving tumble turn performance in swimming - about the impact of wall contact time and tuck index - David, S.; Grove, T.; van Duijven, M.; Koster, P.; Beek, P. J. (ISBS Proceedings Archive (Michigan), 2022)
Race time can be shortened by improving turn performance in competitive swimming, but this requires insight into the optimal turn technique. This study aimed to experimentally investigate the effect of wall contact time (WCT) and Tuck Index on the tumble turn performance. Eighteen Dutch national level swimmers participated and conducted tumble turns with three different WCTs and Tuck Indices. The results showed that a sufficiently long WCT that allows time to generate a high push-off force at the end of the wall contact when the body is in a proper streamlined position. The results also showed that it is possible to recommend an optimal Tuck Index for individual swimmers, which might help to improve their tumble turn and thus their race performance. These results should be verified by an intervention study in which the swimmers are trained to perform the tumble turn with the recommended WCTs and Tuck Indices.